O USO DE BIM NA AVALIAÇÃO DA ENERGIA INCORPORADA E EMISSÕES DE CO2 DE MATERIAIS RECICLADOS E CONVENCIONAIS - Dezen-kempter, Eloisa; Amaral, Elter S.; Gomes, Adriana; Vilhena, Matheus; Oliveira, Lucas V. N.; Rossi, Bruna C. de A. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Buildings life cycle (from construction to deconstruction) consume approximately half of global energy each year, and most of them come from fossil fuels. The construction activities also account for the most significant share of total raw material extraction, waste production, and greenhouse gas (GHG) emissions. A building consumes embodied and operating energy over its life cycle. Embodied Energy is the sum of primary energy (construction materials, products, and processes) and the energy-related with transportation, management, and administration, consumed in the building construction. To quantify environmental impacts of a building, researchers have concentrated more endeavors on operating energy than embodied energy. Few efforts have been undertaken to minimize embodied energy. To address these issues, this paper presents a framework to integrate embodied energy and GHG data into a BIM authoring tool (Autodesk Revit). A comparative analysis was performed between five models of construction with different finishes and specifications, especially with regard to the embodied energy and GHG emissions by the different construction materials. The Results show that a building's energy use and carbon footprint can be reduced during the design phase by accounting the impact of individual material in the supply chain.